2015
DOI: 10.1007/s12020-015-0631-9
|View full text |Cite
|
Sign up to set email alerts
|

γδ Τ cells enhance B cells for antibody production in Hashimoto’s thyroiditis, and retinoic acid induces apoptosis of the γδ Τ cell

Abstract: TCR γδ(+) Τ cells are important in the pathogenesis of inflammatory and autoimmune conditions. This study investigated the effect of γδ T cells on autoantibody production in patients with Hashimoto's thyroiditis (HT). A total of 148 subjects were enrolled, including 99 patients with HT, 5 with simple goiters, and 44 healthy controls. Peripheral blood and thyroid mononuclear cells were subjected to flow cytometric analysis. Thyroid tissues underwent immunofluorescent staining and immunohistochemistry for γδ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Thyroid glands were obtained from 10 patients with HT (10 females, aged 34–61; mean age 48.1 ± 2.9 years) who underwent a thyroidectomy. An HT diagnosis was made based on clinical evaluations and Japanese guidelines as described previously ( 3 , 42 ). All patients were not taking any anti-cytokine therapy and other drugs affecting thyroid function at the time of sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid glands were obtained from 10 patients with HT (10 females, aged 34–61; mean age 48.1 ± 2.9 years) who underwent a thyroidectomy. An HT diagnosis was made based on clinical evaluations and Japanese guidelines as described previously ( 3 , 42 ). All patients were not taking any anti-cytokine therapy and other drugs affecting thyroid function at the time of sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Hashimoto’s thyroiditis (HT) is one of the most common organ-specific autoimmune diseases and is induced by the loss of immune tolerance for the thyroid gland ( 1 ). It is characterized by diffuse infiltration of the thyroid by lymphocytes, destruction of the thyroid gland structure, and autoantibody production ( 2 , 3 ). However, this needs to be further explored, as HT remains a widespread and multifaceted disease of unknown pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid glands were obtained from 6 patients with HT who underwent thyroidectomy. HT diagnosis was made based on clinical evaluations and Japanese guidelines as described previously ( 24 , 25 ). Thyroid tissues from 5 patients with a simple goitre were used as controls based on clinical evaluations and laboratory findings.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens of thyroid tissues were obtained from five patients with HT who underwent thyroidectomy and five multinodular goiters used as controls based on documented clinical evaluations. The diagnoses of HT were based on clinical criteria and Japanese guidelines as described previously [25,26]. All samples were confirmed by pathology obtained in accordance with the regulations and approval of the Institutional Review Board of the Affiliated Hospital of Jiangsu University, shown in the Supplemental file.…”
Section: Preparation Of Tissue Samplesmentioning
confidence: 99%